Political Thuggery and Violence in Gombe of Nigeria: an Examination of Kalare Phenomenon - Umar Alhaji, Abubakar; Rabiu Hashidu, Bala; Ahmed , Abdulkadir; Boyi, Ramatu (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Political thuggery is an integral form of violence where individuals who are seen as thugs move around the streets, homes and markets to inflict injuries, fear, and even kill other people that consequently result to loss of lives and properties especially during elections. The behaviour mostly manifested during elections periods in order to get certain political interests so as to win or maintain political power. This paper examines the causes of political thuggery otherwise called Kalare in Gombe of Nigeria. A total number of 384 respondents were drawn from the sample within the study area. The study instrument with reliability confidence of 95% is used in the process of data collection. The paper uses survey research technique where data are collected using questionnaire and quantitatively analysed. The results reveal that selfish interest of thugs, poverty and unemployment, illiteracy, poor governance; group sentiment and injustice jointly cause political thuggery and violence in Gombe of Nigeria. These lead to creation of fear amongst candidates, hindrance of electorates, killing of innocent people, violating human rights, destruction of valuable properties, insecurity during and after elections, stealing and assault. Therefore, the paper recommends among other things, provision of employment, orientation toward peaceful coexistence, good governance, equity and justice as well as proper education.